(untitled) (Anclajes, 2020)
The main aim of this work is to identify a narrative space in which two different traditions come together, the Hispanic legitimized one and the original peoples’ subordinated to colonial practices. From the study of the Salamanca subject matter, we propose to go deeply into the recollections and the collective memory of the symbolic processes that tend to become invisible by the cultural hegemony of European origin. The analysed corpus is made up of Tehuelche testimonies compiled in the 60s by linguist Jorge Suárez and unpublished until 2006 (Fernández Garay y Hernández), and some oral texts recorded among internal migrants of the Argentine Patagonia and Chile in the context of “Workshops of History and Memory,” during an adults’ lit-eracy course, in which most participants proclaimed themselves as mapuches. (Bahía Blanca, Buenos Aires Province, 1995-2012).